2023
DOI: 10.3390/molecules28104187
|View full text |Cite
|
Sign up to set email alerts
|

Coriander (Coriandrum sativum) Polyphenols and Their Nutraceutical Value against Obesity and Metabolic Syndrome

Abstract: Coriander is a widely used plant for its medicinal and biological properties. Both coriander essential oil and extracts are interesting sources of bioactive compounds and are widely used as spices in culinary practice due to their exclusive aroma and flavour. We focus our attention on coriander extracts that are rich in polyphenols. It is well known that plant polyphenols possess different biological activities and several functional foods contain this class of compounds. The polyphenol profile in an extract c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…In a research study, rats given coriander seeds had their LDL (bad) cholesterol significantly reduced and their HDL (good) cholesterol significantly increased. Furthermore, in rat models of general anaesthesia, a crude extract of Coriandrum sativum was found to have antihypertensive effects, leading to a reduction in blood pressure due to the relaxation of arterial contractions [41][42][43][44][45] . Coriander is shown in a symbolic context below 27 (Figure 5).…”
Section: Coriandermentioning
confidence: 99%
“…In a research study, rats given coriander seeds had their LDL (bad) cholesterol significantly reduced and their HDL (good) cholesterol significantly increased. Furthermore, in rat models of general anaesthesia, a crude extract of Coriandrum sativum was found to have antihypertensive effects, leading to a reduction in blood pressure due to the relaxation of arterial contractions [41][42][43][44][45] . Coriander is shown in a symbolic context below 27 (Figure 5).…”
Section: Coriandermentioning
confidence: 99%
“…Coriander is known to effectively treat a variety of conditions in the urinary, skin, cardiovascular, digestive, and respiratory systems. It is also used to cure diabetes, dyspepsia, flatulence, and diarrhea diseases (Pandey et al., 2023 ; Scandar et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted by Ashika et al [8], coriander leaves contain vanillic, p-coumaric, cisferulic, and trans-ferulic acids, which are responsible for the antioxidant properties of the plant. Additionally, Scandar et al [9] found that the leaves and stems of coriander are the most nutritious and beneficial parts of the plant. Nhut et al [10] found that coriander leaves contain rutin, a type of flavonoid that has antioxidant, anti-inflammatory, and anti-cancer properties.…”
Section: Introductionmentioning
confidence: 99%